A Multimodal Multi‐institutional Solution to Remote Medical Student Education for Otolaryngology During COVID‐19. (9th June 2020) - Ruthberg, Jeremy S.; Quereshy, Humzah A.; Ahmadmehrabi, Shadi; Trudeau, Stephen; Chaudry, Emaan; Hair, Bryan; Kominsky, Alan; Otteson, Todd D.; Bryson, Paul C.; Mowry, Sarah E.
Abstract : During the coronavirus 2019 pandemic, there has been a surge in production of remote learning materials for continued otolaryngology resident education. Medical students traditionally rely on elective and away subinternship experiences for exposure to the specialty. Delays and cancellation of clinical rotations have forced medical students to pursue opportunities outside of the traditional learning paradigm. In this commentary, we discuss the multi‐institutional development of a robust syllabus for medical students using a multimodal collection of resources. Medical students collaborated with faculty and residents from 2 major academic centers to identify essential otolaryngology topics. High‐quality, publicly available, and open‐access content from multiple sources were incorporated into a curriculum that appeals to a variety of learners. Multimodal remote education strategies can be used as a foundation for further innovation aimed at developing tomorrow's otolaryngologists.